2007
DOI: 10.1108/01425450710826131
|View full text |Cite
|
Sign up to set email alerts
|

Psychological climate and individual performance in India: test of a mediated model

Abstract: Purpose -The purpose of this study is to investigate the relationship between psychological climate and employee performance, in the Indian environment, in order to understand better the conditions that foster high levels of in-role and extra-role performance. Design/methodology/approach -Based on a literature review, the paper includes organizational citizenship behaviour (OCB) and job satisfaction as mediating variables. Further, it uses data obtained from 357 managerial employees in the manufacturing and se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
40
0
4

Year Published

2009
2009
2015
2015

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 67 publications
(48 citation statements)
references
References 48 publications
4
40
0
4
Order By: Relevance
“…Contextual modifi cations in the Indian business domain especially over the past one decade have undergone radical transformations that have had their impact on management policies and practice particularly those related to the utilization of the human resources (Biswas & Varma, 2007;Rao, 1999Rao, , 2003. Earlier assumptions about human resource development and its consequence on quality of work life has been proved to be true in various organizations where HR practices have shifted focus from purely administrative and documentation functions to optimal (human) resource utilization.…”
Section: Conceptual Considerationsmentioning
confidence: 99%
“…Contextual modifi cations in the Indian business domain especially over the past one decade have undergone radical transformations that have had their impact on management policies and practice particularly those related to the utilization of the human resources (Biswas & Varma, 2007;Rao, 1999Rao, , 2003. Earlier assumptions about human resource development and its consequence on quality of work life has been proved to be true in various organizations where HR practices have shifted focus from purely administrative and documentation functions to optimal (human) resource utilization.…”
Section: Conceptual Considerationsmentioning
confidence: 99%
“…Indeed, within this context, there is an increasing need to study employee-organization social exchange and its impact on individual and organizational outcomes (Biswas & Varma, 2007;Tsui, Pearce, Porter, & Hite, 1995). Additionally, prior research has indicated that within the framework of social exchange theory (SET), organizational justice would be directly associated with the quality of social exchange between individuals and their organizations and also organizational agents such as immediate supervisors (Bhatnagar & Biswas, 2010).…”
mentioning
confidence: 99%
“…These include, for example, performance management, training and development, diversity management, and employee recognition (e.g., Bhatnagar, 2007a;Chand, 2010). These studies have pointed to a similar conclusion that firms with a strategic HR orientation perform significantly better than those with less emphasis on HR do (e.g., Bhatnagar, 2007b;Biswas & Varma, 2007). For example, Tymon, Stumpf, and Doh's (2010) study of over 4,000 professional employees in the BPO sector showed that the intrinsic rewards experienced were critical to employee retention, satisfaction with the organization, and career success.…”
Section: Employer Hr Strategymentioning
confidence: 89%